THE INFLUENCE OF WORK MOTIVATION AND DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES OF PERUMDA TIRTA BENTENG, TANGERANG CITY - Hsb, Kamsanuddin; Amanu, Muhammad (Dynamic Management Journal, 2024)
The purpose of this research is to determine the influence of Motivation and Work Discipline on the Performance of Employees at Perumda Tirta Benteng, Tangerang City. This research is classified as quantitative research involving a population of 60 people. Since the population was less than 100 people, sampling was carried out using a saturated sampling technique so that samples were taken from the total population of 60 people. Data collection techniques through distributing questionnaires. The analysis technique uses SPSS version 25 software. Based on partial hypothesis testing (t test) it turns out that Motivation (X1) has a positive and significant effect on Performance (Y), indicated by tcount>ttable (5.573>2.002) and significance <0.05 (0.000<0.005). Work Discipline (X2) has a positive and significant effect on Performance (Y), shown by the test results where tcount>ttable (6.811>2.002), and significance <0.05 (0.000<0.005). Meanwhile, simultaneously (F test) it is known that Motivation (X1) and Work Discipline (X2) together have a positive and significant effect on Performance (Y), as evidenced by Fcount>Ftable (32.745>3.16) with a significance of <0.005 (0.000<0.005). The multiple linear regression equation is Y = 8.007+0.357(X1)+0.442(X2).